UNDERGROUND METEOROLOGY-“What’s the weather underground?” - Badino, Giovanni (Acta Carsologica, 2010)
The aim of this work is to provide a synthetic outline of some of the processes of transient nature occurring in caves, focusing on poorly studied general aspects of underground physics and mainly making use of original experimental data. In the first part, the average climatic conditions of a caves, their connection to the external climate, and the general role played by rock, water, air and external morphology are discussed. The variation of the internal temperature withthe altitude is a key parameter for the cave physics: the related energetic consequences are briefly discussed. In the second part, transient processes are considered, and a general overview of main meteorological phenomena occurring underground is given. The physics of thermal sedimentation, of underground temperature ranges, of infrasonic oscillations of cave atmospheres and, above all, of water vapour condensation in caves is synthetically described. The experimental study of these processes is extremely difficult, because they are time dependent and have very small amplitude; the first measurements show, however, that their variability from one cave to another, and from point to point inside a cave, is surprisingly high. To provide a more correct interpretation of underground climatic measurements, for their speleogenetic role and importance in cave environment protection, a better understanding of the processes described here is essential.